Rekayasa Lingkungan Melalui Domestikasi Salinitas Terhadap Pertumbuhan dan Kelangsungan Hidup Ikan Badut (Amphiprion melanopus) - Amelya Mustamu; Mulis Mulis; Sutianto Pratama Suherman (Jurnal Perikanan Unram, 2024)
Clown fish (Amphiprion melanopus) is one of the ornamental fish that is in great demand because of its shape, color, uniqueness and active movements. Salinity is an important indicator that can influence the growth and survival of clownfish during the rearing period. This research aims to determine the effect of environmental engineering through salinity domestication on the growth and survival of clownfish. The method used in this research was a completely randomized design (CRD) method with 4 treatments repeated 3 times. The treatments used were 4 different salinities. Treatment A = 30 ppt (control), Treatment B = 25 ppt, Treatment C = 20 ppt, Treatment D = 15 ppt. The results of calculating the average growth in weight and length of clownfish obtained the best results in treatment A, while the average growth in length and weight was the lowest in treatment D. The survival rate during the study showed that in treatment A it was 83%, treatment B and C by 75% and treatment D by 67%. Based on the results of this research, it shows that environmental engineering through salinity domestication has a real influence on the growth in length and weight of clownfish, while survival rate does not have a real influence. This shows that clownfish can still adapt and can survive up to a salinity of 20 ppt with a survival rate of 75%.